ATTITUDES OF THE STUDENTS AT THE HIGHER SCHOOL OF TOURISM PROFESSIONS OF RHODES REGARDING SUSTAINABLE DEVELOPMENT - Bentsou, Dimitra (PROFESSIONAL STUDIES: Theory And Practice, 2022)
In recent years, the constant degradation of the natural environment has led the consumers to make more environmentally friendly choices. Therefore, in the field of tourism, the tourists have turned to more environmentally friendly vacations by choosing accommodation that respects the environment. Tourism professionals and students at tourism schools should be informed about sustainable development through the training they receive to form the attitudes to promote it. In the present study, research data revealed a discrepancy between the knowledge of first-year students and third-year students, proving that in the previous levels of education there was no information about sustainable development. In addition, it seems that third-year students can recognize the value of sustainable development for the operation of hotels